BIOPLASTIC FROM TAPIOCA STARCH WASTE AND RICE WASTE - Sri Widyastuti; Yitno Utomo; Annisa Firdayanti; Rhenny Ratnawati; Umi Solikah (Universitas Trisakti, 2024)
Bioplastic is a plastic that is easily decomposed naturally by the activity of microorganisms without leaving toxic residues because of its that can return to nature. Aim: This study aim to examine the quality of bioplastics from variations of tapioca starch and rice waste raw materials for optimal composition. Methodology and Results: The method used is by mixing the raw material of tapioca starch waste and rice waste with variations in the composition of the material; 100% rice waste, 100% tapioca starch waste, 30% tapioca starch waste: 70% rice waste, 50% tapioca starch waste: 50% rice waste, 70% tapioca starch waste: 30% rice waste. Add 10 mL of glycerol, 30 mL of distilled water, 40 mL of acetate solvent, and 40 ml of 96% ethanol. The product will be tested on a laboratory scale for tensile strength, elongation at break, FTIR tests, and biodegradation according to SNI 7188.7:2016 for the bioplastic category that is easily biodegradable. The result shows that the optimal composition was found in the composition of 100% rice waste raw material with the quality of the tensile strength test results of 3,45 MPa, the value of elongation at break 3,8%, and the value of biodegradation 100%. The resulting bioplastics contain functional groups O-H (hydroxyl) bonded to hydrogen, C-H (alkanes), C≡C (alkynes), esters, simple aromatic compounds, C-O (carboxyl), C=C (alkenes), and hydrocarbons -(CH2)n. Conclusion, significance, and impact of study: The use of starch to produce biodegradable materials is because it is environmentally friendly, easily degraded, available in large quantities, and affordable, moreover, the bioplastics derived from these waste sources are typically biodegradable, meaning they can break down into natural compounds under certain conditions, reducing environmental pollution.